2022
DOI: 10.1002/hpja.610
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to COVID‐19 information by ensuring the readability of government websites

Abstract: Issue addressed This study evaluated the readability of web pages from two public‐facing Victorian government websites that were responsible for communicating key health messages relating to the COVID‐19 pandemic in 2020. Methods Webpages were downloaded and filtered to identify relevant materials (English language materials containing HTML files that referred to COVID‐19). The files were converted to text files and two Python packages, SpaCy and TextStat were used to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The readability level of the materials was lower at the advanced level. These findings were consistent with those of previous studies examining online information on COVID-19, which showed that the analyzed webpages mostly required a higher reading level than the recommended six-grade reading level [20][21][22][23][24]. This poor readability level is concerning because laypeople considered materials from local governments as a major source of health information during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…The readability level of the materials was lower at the advanced level. These findings were consistent with those of previous studies examining online information on COVID-19, which showed that the analyzed webpages mostly required a higher reading level than the recommended six-grade reading level [20][21][22][23][24]. This poor readability level is concerning because laypeople considered materials from local governments as a major source of health information during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%